Porous resin film for metal layer laminate and metal layer laminate
A porous resin film with controlled thermal expansion coefficients addresses the issue of copper layer damage in copper-clad laminates, enhancing electrical connection reliability by suppressing stress on metal layers.
Patent Information
- Application Number
- JP2021070654
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-19
- Publication Date
- 2025-12-18
- Estimated Expiration
- 2041-04-19
AI Technical Summary
The copper layer pattern in existing copper-clad laminates is prone to damage during reflow, leading to reduced reliability of electrical connections in high-temperature environments.
A porous resin film with a specific thermal expansion coefficient ratio (Z/X ≤ 3.5) is used to suppress stress on metal layers within through holes, ensuring the laminate's electrical connection reliability.
The laminate maintains excellent electrical connection reliability by minimizing damage to metal layers in high-temperature environments.
Smart Images

Figure 0007788222000002 
Figure 0007788222000003 
Figure 0007788222000004
Abstract
Description
[Technical Field]
[0001] The present invention relates to a porous resin film for a metal layer laminate and a metal layer laminate. [Background technology]
[0002] It is known to use a polyimide porous film in a copper layer laminate (see, for example, Patent Document 1 below). A copper-clad laminate comprises a polyimide porous film having through holes, copper layers laminated on both sides of the film in the thickness direction, and copper-plated portions that electrically connect the two and are disposed on the inner surfaces of the through holes. In a copper-clad laminate, the copper layer is formed into a pattern by etching and electrically connected to another substrate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] WO2018 / 186486 Summary of the Invention [Problem to be solved by the invention]
[0004] When the copper layer pattern of Patent Document 1 is electrically connected to another substrate by reflow, the copper-plated portion is easily damaged, which causes a problem of reduced reliability of electrical connection between the patterns arranged on both sides of the polyimide porous film.
[0005] The present invention provides a porous resin film for metal layer laminates and a metal layer laminate that can suppress damage to the metal layer arranged on the inner surface of a through hole even in a high-temperature environment and have excellent electrical connection reliability. [Means for solving the problem]
[0006] The present invention (1) is a porous resin film for a metal layer laminate used for laminating a metal layer, and includes a porous resin film for a metal layer laminate having a minimum thermal expansion coefficient X in a plane direction perpendicular to the thickness direction and a thermal expansion coefficient Z in the thickness direction, and the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is 3.5 or less.
[0007] In this porous resin film for metal layer laminates, the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is low, at 3.5 or less, so that the stress applied to the metal layer disposed on the inner circumferential surface of the through hole can be suppressed in a high-temperature environment. Therefore, the damage to the metal layer can be suppressed. As a result, a metal layer laminate with excellent electrical connection reliability can be produced.
[0008] The present invention (2) includes the metal layer laminate described in (1), which has a through hole penetrating through the thickness direction and comprises a porous resin film for the metal layer laminate, and a metal layer arranged on one side and the other side of the porous resin film for the metal layer laminate in the thickness direction and on the inner surface of the through hole.
[0009] In this metal layer laminate, damage to the metal layer is suppressed, and therefore this metal layer laminate has excellent electrical connection reliability. [Effects of the Invention]
[0010] The porous resin film for a metal layer laminate and the metal layer laminate of the present invention can suppress damage to the metal layer arranged on the inner circumferential surface of the through hole even in a high temperature environment, and have excellent electrical connection reliability. [Brief explanation of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view of one embodiment of the porous resin film for metal layer laminates of the present invention. [Figure 2] FIG. 2 is a cross-sectional view of a metal layer laminate provided with the porous resin film for a metal layer laminate shown in FIG. 1, in which no through-holes have yet been formed. [Figure 3]FIG. 3 is a cross-sectional view of a metal layer laminate in which a through hole is formed. DETAILED DESCRIPTION OF THE INVENTION
[0012] One embodiment of the porous resin film for metal layer laminate of the present invention will be described with reference to Fig. 1. As shown in Fig. 1, the porous resin film for metal layer laminate 1 has a thickness and extends in a plane direction perpendicular to the thickness direction. The thickness of the porous resin film for metal layer laminate 1 is not particularly limited. The thickness of the porous resin film for metal layer laminate 1 is, for example, 2 µm or more, preferably 5 µm or more, and for example, 1,000 µm or less, preferably 500 µm or less.
[0013] <Thermal expansion coefficient> The porous resin film 1 for a metal layer laminate has a minimum thermal expansion coefficient X in the planar direction and a thermal expansion coefficient Z in the thickness direction.
[0014] The minimum thermal expansion coefficient X is the lowest thermal expansion coefficient among any of the in-plane directions. The minimum thermal expansion coefficient X is not particularly limited as long as it satisfies the ratio (Z / X) described below. The minimum thermal expansion coefficient X is, for example, 30.0 ppm / K or less, preferably 25.0 ppm / K or less. The lower limit of the minimum thermal expansion coefficient X is not particularly limited. The lower limit of the minimum thermal expansion coefficient X is, for example, 1 ppm / K or 10 ppm / K. The method for measuring the minimum thermal expansion coefficient X will be described in the Examples below.
[0015] The thermal expansion coefficient Z in the thickness direction is not particularly limited as long as it satisfies the ratio (Z / X) described below. The thermal expansion coefficient Z in the thickness direction is, for example, greater than the minimum thermal expansion coefficient X described above. Specifically, the thermal expansion coefficient Z in the thickness direction is, for example, 100 ppm / K or less, preferably 90 ppm / K or less, more preferably 80 ppm / K or less, even more preferably 70 ppm / K or less, and particularly preferably 60 ppm / K or less. If the thermal expansion coefficient Z in the thickness direction is equal to or less than the upper limit described above, the ratio (Z / X) described below can be set within a desired range, i.e., a low ratio (Z / X). The lower limit of the thermal expansion coefficient Z in the thickness direction is not particularly limited. The lower limit of the thermal expansion coefficient Z in the thickness direction is, for example, 1 ppm / K or 10 ppm / K. A method for measuring the thermal expansion coefficient Z in the thickness direction will be described in the Examples described later.
[0016] The ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is 3.5 or less.
[0017] If the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X exceeds 3.5, the expansion of the porous resin film 1 for metal layer laminates in the thickness direction relative to the expansion in the plane direction of the porous resin film 1 for metal layer laminates at high temperatures becomes excessive. Therefore, when a metal layer laminate 10 including a porous resin film 1 for metal layer laminates having through holes 9 has conductive portions 5 formed in the through holes 9 and the metal layer laminate 10 is placed in a high-temperature environment, the conductive portions 5 are damaged. This reduces the electrical connection reliability of the metal layer laminate 10. In other words, in this porous resin film 1 for metal layer laminates, the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is small, at 3.5 or less, and therefore the expansion of the porous resin film 1 for metal layer laminates in the thickness direction relative to the expansion in the plane direction of the porous resin film 1 for metal layer laminates at high temperatures can be suppressed. Therefore, even if the metal layer laminate 10 is placed in a high-temperature environment, damage to the conductive parts 5 can be suppressed. As a result, a decrease in the electrical connection reliability of the metal layer laminate 10 can be suppressed.
[0018] The ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is preferably 3.0 or less. The lower limit of the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is not particularly limited. The lower limit of the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is, for example, 1, or 1.5, or even 2.0.
[0019] The porous resin film 1 for a metal layer laminate is porous and has closed cells and / or open cells.
[0020] The porosity of the porous resin film 1 for metal layer laminates is, for example, 50% or more, preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. The porosity of the porous resin film 1 for metal layer laminates is, for example, less than 100%, or even 99% or less. A method for measuring the porosity of the porous resin film 1 for metal layer laminates will be described in the Examples below.
[0021] The porosity of the porous resin film 1 for metal layer laminates is adjusted by the type and / or amount of a porosifying agent (described later).
[0022] The dielectric constant of the porous resin film 1 for metal layer laminates at a frequency of 60 GHz is, for example, 2.5 or less, preferably 1.9 or less, more preferably 1.6 or less, and is, for example, more than 1.0. The dielectric constant of the porous resin film 1 for metal layer laminates is actually measured by a resonator method using a frequency of 60 GHz.
[0023] The dielectric loss tangent of the porous resin film 1 for metal layer laminates at a frequency of 60 GHz is, for example, 0.006 or less, and for example, exceeds 0. The dielectric loss tangent of the porous resin film 1 for metal layer laminates is actually measured by a resonator method using a frequency of 60 GHz.
[0024] Examples of materials for the porous resin film 1 for metal layer laminates include thermosetting resins.
[0025] Examples of thermosetting resins include polycarbonate resins, polyimide resins, fluorinated polyimide resins, epoxy resins, phenolic resins, urea resins, melamine resins, diallyl phthalate resins, silicone resins, thermosetting urethane resins, fluororesins (fluorine-containing olefin polymers (specifically, polytetrafluoroethylene (PTFE))), and liquid crystal polymers (LCPs). These can be used alone or in combination of two or more.
[0026] Among the above resins, polyimide resins are preferred from the viewpoint of mechanical strength. Details of polyimide resins, including their physical properties and production methods, are described in, for example, WO2018 / 186486.
[0027] The porous resin film 1 for a metal layer laminate can have skin layers (not shown) formed on one and the other surfaces in the thickness direction.
[0028] Next, a method for producing the porous resin film 1 for a metal layer laminate will be described.
[0029] Specifically, first, the base film 2 is prepared. The base film 2 extends in the planar direction. Examples of materials for the base film 2 include metal and resin. Preferably, the base film 2 is a metal, since it can be reused as the first metal layer 11 (see FIG. 2) in the metal layer laminate 10. Examples of metals include copper, iron, silver, gold, aluminum, nickel, and alloys thereof (stainless steel, bronze). Preferably, the metal is copper. The thickness of the base film 2 is, for example, 0.1 μm or more, preferably 1 μm or more, and for example, 100 μm or less, preferably 50 μm or less.
[0030] Next, a varnish containing the resin precursor, a porosifying agent, a nucleating agent, and a solvent is prepared, and the varnish is then applied to one surface of the substrate film 2 in the thickness direction to form a coating. The types and blending ratios of the porosifying agent, nucleating agent, and solvent in the varnish are described, for example, in WO2018 / 186486. In particular, the number of parts by mass (blending ratio) of the porosifying agent is preferably 20 parts by mass or more, more preferably 100 parts by mass or more, and preferably 300 parts by mass or less, more preferably 250 parts by mass or less, per 100 parts by mass of the precursor.
[0031] The case where the resin is a polyimide resin will be described. The precursor of the polyimide resin is, for example, a reaction product of a diamine component and an acid dianhydride component. Examples of the diamine component include aromatic diamines, aliphatic diamines, and alicyclic diamines. A preferred example of the diamine component is an aromatic diamine.
[0032] Aromatic diamines include primary, secondary, and tertiary diamines.
[0033] The first diamine contains a single aromatic ring. Examples of the first diamine include phenylenediamine, dimethylbenzenediamine, and ethylmethylbenzenediamine. From the viewpoint of mechanical strength, phenylenediamine is preferred. Examples of the phenylenediamine include o-phenylenediamine, m-phenylenediamine, and p-phenylenediamine. Examples of the phenylenediamine include p-phenylenediamine.
[0034] The second diamine contains a plurality of aromatic rings and ether bonds disposed between them. Examples of the second diamine include oxydianiline. Examples of the oxydianiline include 3,4'-oxydianiline and 4,4'-oxydianiline. From the viewpoint of mechanical strength, 4,4'-oxydianiline is preferred.
[0035] The tertiary diamine contains a plurality of aromatic rings and ester bonds disposed between them. The tertiary diamine is a component that reduces the ratio (Z / X) of the thermal expansion coefficients in the porous resin film for metal layer laminates 1. Examples of the tertiary diamine include aminophenyl aminobenzoate, and preferably 4-aminophenyl-4-aminobenzoate.
[0036] In addition to the primary to tertiary diamines, examples of the aromatic diamine include 4,4'-methylenedianiline, 4,4'-dimethylenedianiline, 4,4'-trimethylenedianiline, and bis(4-aminophenyl)sulfone.
[0037] The diamine components described above can be used alone or in combination. A preferred diamine component is a combination of a primary diamine, a secondary diamine, and a tertiary diamine. A more preferred diamine is a combination of p-phenylenediamine, 4,4'-oxydianiline, and 4-aminophenyl-4-aminobenzoate.
[0038] p-Phenylenediamine is sometimes abbreviated as PDA, 4,4'-oxydianiline (also known as 4,4'-diaminophenyl ether) is sometimes abbreviated as ODA, and 4-aminophenyl-4-aminobenzoate is sometimes abbreviated as APAB.
[0039] The molar fraction of the first diamine in the diamine component is preferably 10 mol% or more, more preferably 20 mol% or more, and for example, 70 mol% or less, preferably 65 mol% or less. The molar fraction of the second diamine in the diamine component is preferably 5 mol% or more, more preferably 10 mol% or more, and for example, 40 mol% or less, preferably 30 mol% or less. The molar fraction of the tertiary diamine in the diamine component is preferably 5 mol% or more, more preferably 10 mol% or more, and for example, 40 mol% or less, preferably 30 mol% or less.
[0040] <Acid dianhydride component> The acid dianhydride component contains, for example, an acid dianhydride containing an aromatic ring. Examples of the acid dianhydride containing an aromatic ring include aromatic tetracarboxylic dianhydrides. Examples of the aromatic tetracarboxylic dianhydrides include benzenetetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, biphenylsulfonetetracarboxylic dianhydride, and naphthalenetetracarboxylic dianhydride.
[0041] Examples of benzenetetracarboxylic dianhydrides include benzene-1,2,4,5-tetracarboxylic dianhydride (also known as pyromelotic dianhydride). Examples of benzophenonetetracarboxylic dianhydrides include 3,3'-4,4'-benzophenonetetracarboxylic dianhydride. Examples of biphenyltetracarboxylic dianhydrides include 3,3'-4,4'-biphenyltetracarboxylic dianhydride, 2,2'-3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, and 3,3',4,4'-diphenylethertetracarboxylic dianhydride. Examples of biphenylsulfonetetracarboxylic dianhydrides include 3,3',4,4'-biphenylsulfonetetracarboxylic dianhydride. Examples of naphthalenetetracarboxylic dianhydrides include 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,2,4,5-naphthalenetetracarboxylic dianhydride, and 1,4,5,8-naphthalenetetracarboxylic dianhydride. These can be used alone or in combination. From the viewpoint of mechanical strength, the dianhydride component is preferably biphenyltetracarboxylic dianhydride, and more preferably 3,3'-4,4'-biphenyltetracarboxylic dianhydride. 3,3'-4,4'-biphenyltetracarboxylic dianhydride is sometimes abbreviated as BPDA.
[0042] The ratio of the diamine component to the acid dianhydride component is adjusted so that the molar amount of the amino group (-NH2) of the diamine component and the molar amount of the acid anhydride group (-CO-O-CO-) of the acid dianhydride component are, for example, equal.
[0043] To prepare a polyimide resin precursor, the diamine component, the acid dianhydride component, and a solvent are mixed to prepare a varnish, and the varnish is heated to prepare a precursor solution. Next, a nucleating agent and a porosifying agent are mixed into the precursor solution to prepare a porous precursor solution. The porous precursor solution is then applied to one surface in the thickness direction of the substrate film 2 to form a coating film.
[0044] The coating is then dried by heating to form a precursor film, which is a precursor film having a phase-separated structure of the polyimide resin precursor and the porosifying agent, with the nucleating agent as the core, while the solvent is removed by the heating.
[0045] Thereafter, the porosifying agent is extracted (pulled out or removed) from the precursor film by, for example, supercritical extraction using supercritical carbon dioxide as a solvent.
[0046] Thereafter, the precursor film is cured by heating to form a porous resin film 1 for a metal layer laminate made of polyimide resin. The other surface of this porous resin film 1 for a metal layer laminate is in contact with the base film 2 in the thickness direction.
[0047] Thereafter, if necessary, the substrate film 2 is removed as shown by the solid line in Fig. 1. For example, if the material of the substrate film 2 is metal, the substrate film 2 is dissolved using a stripping liquid. Examples of the stripping liquid include FeCl3. In this way, a porous resin film 1 for metal layer laminates is obtained.
[0048] Next, a metal layer laminate 5 including the porous resin film for metal layer laminate 1 will be described as shown in Fig. 3. This metal layer laminate 10 includes the porous resin film for metal layer laminate 1 and a metal layer 4.
[0049] The porous resin film 1 for a metal layer laminate includes through holes 9. The through holes 9 penetrate the porous resin film 1 for a metal layer laminate in the thickness direction. The shape and dimensions of the through holes 9 in a plan view are not particularly limited.
[0050] The metal layer 4 integrally includes a first metal layer 11, a second metal layer 12, and a conductive portion 5.
[0051] The first metal layer 11 is disposed on the other surface in the thickness direction of the porous resin film for metal layer laminates 1. Examples of materials for the first metal layer 11 include the metals exemplified for the base film 2. Preferably, copper is used. The thickness of the first metal layer 11 is, for example, 0.1 μm or more, preferably 1 μm or more, and for example, 100 μm or less, preferably 50 μm or less.
[0052] The second metal layer 12 is disposed on one surface in the thickness direction of the porous resin film 1 for metal layer laminates. The second metal layer 12 may be disposed on one surface in the thickness direction of the porous resin film 1 for metal layer laminates via an adhesive layer (not shown). Materials for the first metal layer 11 include the metals exemplified for the substrate film 2. Preferably, copper is used. The thickness of the second metal layer 12 is, for example, 0.1 μm or more, preferably 1 μm or more, and for example, 100 μm or less, preferably 50 μm or less.
[0053] The conductive portion 5 is disposed on the inner circumferential surface 7 of the porous resin film 1 for metal layer laminates, facing the through hole 9. Specifically, the conductive portion 5 is in contact with the inner circumferential surface 7. The conductive portion 5 connects the first metal layer 11 and the second metal layer facing the through hole 9. As a result, the conductive portion 5 electrically connects the first metal layer 11 and the second metal layer 12. The material of the conductive portion 5 is the same as the material of the first metal layer 11. The thickness of the conductive portion 5 is, for example, 1 μm or less, preferably 10 μm or less, and for example, 500 μm or more, preferably 250 μm or more. The thickness of the conductive portion 5 is the length from the inner circumferential surface 7 toward the inside of the through hole 9.
[0054] A method for producing a metal layer laminate 10 will be described. First, a laminate 8 is prepared, which includes a porous resin film 1 for a metal layer laminate, a first metal layer 11, and a second metal layer 12, as shown in FIG. 2. If the material of the base film 2 is metal, the base film 2 is not removed and is used as is as the first metal layer 11. Meanwhile, a second metal layer 12 is disposed on one surface in the thickness direction of the porous resin film 1 for a metal layer laminate. This results in a porous resin film 1 for a metal layer laminate sandwiched between the first metal layer 11 and the second metal layer 12 in the thickness direction, as shown in FIG. 2.
[0055] 3, through holes 9 are formed so as to penetrate the laminate 8 in the thickness direction. Methods for forming the through holes 9 include, for example, drilling and laser processing.
[0056] Thereafter, for example, by plating, the conductive portion 5 is formed on the inner circumferential surface 7. The conductive portion 5 has a cylindrical or columnar shape.
[0057] In this way, the metal layer laminate 10 is manufactured.
[0058] Thereafter, the first metal layer 11 and the second metal layer 12 are patterned by etching or the like. After that, the first metal layer 11 is electrically connected to another substrate (not shown) by reflow, for example. The temperature during reflow is, for example, 100°C or higher and 150°C or lower.
[0059] This metal layer laminate 10 is used, for example, in fifth-generation (5G) standard wireless communications and high-speed flexible printed circuit boards (FPCs).
[0060] (Effects of one embodiment) In this porous resin film 1 for metal layer laminates, the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is low, at 3.5 or less. Therefore, stress applied to the conductive parts 5 (metal layers 4 disposed on the inner circumferential surfaces 7 of the through holes 9) in high-temperature environments can be suppressed. Therefore, damage to the conductive parts 5 can be suppressed. Damage includes cracks and disconnections. As a result, a metal layer laminate 10 with excellent electrical connection reliability can be manufactured.
[0061] 3, damage to the conductive parts 5 is suppressed, and therefore, this metal layer laminate 10 has excellent electrical connection reliability.
[0062] (Variation) In the following modifications, the same components and steps as those in the above-described embodiment are denoted by the same reference numerals, and detailed descriptions thereof will be omitted. Furthermore, the modifications can achieve the same effects as those in the above-described embodiment, unless otherwise specified. Furthermore, the embodiment and its modifications can be combined as appropriate. [Example]
[0063] The present invention will be described in more detail below with reference to examples and comparative examples. It should be noted that the present invention is not limited to these examples and comparative examples. The specific numerical values of the blending ratios (content ratios), physical property values, parameters, etc. used in the following description can be substituted with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than" or "exceeding") of the corresponding blending ratios (content ratios), physical property values, parameters, etc. described in the "Description of the Invention" above.
[0064] Example 1 A reactor equipped with a stirrer and a thermometer was charged with 71.37 g (0.66 mol) of PDA, 44.05 g (0.22 mol) of ODA, and 50.22 g (0.22 mol) of APAB, and 2300 g of N-methyl-2-pyrrolidone (NMP) was added as a solvent and stirred to prepare an NMP solution of PDA, ODA, and APAB. The NMP solution contained 1.10 mol of the diamine component.
[0065] Next, 323.64 g (1.10 mol) of 3,3'-4,4'-biphenyltetracarboxylic dianhydride (3,3'-4,4'-BPDA) was gradually added to the NMP solution of PDA, ODA, and APAB, and 331 g of N-methyl-2-pyrrolidone (NMP) was added. The mixture was heated to 80°C and stirred for 10 hours to obtain a polyimide precursor solution.
[0066] To 100 parts by mass of the solids content of the polyimide precursor solution, 3 parts by mass of PTFE powder with a median diameter of 1 μm or less was added as a nucleating agent, 200 parts by mass of polyoxyethylene dimethyl ether (grade: MM400, manufactured by NOF Corporation) with a weight-average molecular weight of 400 as a porosifying agent, and 4 parts by mass of 2-methylimidazole (2Mz-H, manufactured by Shikoku Chemical Industries Co., Ltd.) to obtain a polyimide porous precursor solution. This porous precursor solution was applied to a copper substrate film 2 (first metal layer 11) using a comma method to form a coating. The coating was then dried at 120 to 160°C for approximately 7 minutes to produce a precursor film with a thickness of 50 μm.
[0067] This precursor film was immersed in carbon dioxide pressurized to 30 MPa at 60°C and passed through for 8 hours to promote the extraction and removal of the porosifying agent, phase separation of the remaining NMP, and the formation of pores.The carbon dioxide pressure was then reduced.
[0068] The precursor film was then heat-treated under vacuum at a temperature of 300°C to 400°C for approximately 5 hours to remove remaining components and promote imidization, thereby obtaining a porous resin film 1 for metal layer laminates arranged on one thickness-wise surface of the substrate film 2.
[0069] Thereafter, the substrate film 2 and the porous resin film 1 for a metal layer laminate were immersed in an FeCl3 solution to dissolve and remove the substrate film 2. This produced a porous resin film 1 for a metal layer laminate. The dielectric constant and dielectric loss tangent of the porous resin film 1 for a metal layer laminate at a frequency of 60 GHz were 1.51 and 0.002, respectively.
[0070] Example 2 A porous resin film 1 for metal layer laminates was produced in the same manner as in Example 1. However, the mass part number of polyoxyethylene dimethyl ether was changed from 200 mass parts to 150 mass parts. The dielectric constant and dielectric loss tangent of the porous resin film 1 for metal layer laminates at a frequency of 60 GHz were 1.70 and 0.002, respectively.
[0071] Example 3 A porous resin film 1 for metal layer laminates was produced in the same manner as in Example 1. However, the mass part number of polyoxyethylene dimethyl ether was changed from 200 mass parts to 50 mass parts. The dielectric constant and dielectric loss tangent of the porous resin film 1 for metal layer laminates at a frequency of 60 GHz were 2.00 and 0.002, respectively.
[0072] (Comparative Example 1) A reactor equipped with a stirrer and a thermometer was charged with 1444 g (13.36 mol) of PDA and 669 g (3.34 mol) of ODA, and 28,534 g of NMP was added and stirred to prepare an NMP solution of PDA and ODA. The NMP solution contained 16.70 mol of the diamine component.
[0073] Next, 4913 g (16.70 mol) of BPDA was gradually added to this solution, followed by 3 parts by mass of PTFE powder with a median diameter of 1 μm or less as a nucleating agent and 6658 g of N-methyl-2-pyrrolidone (NMP). The mixture was stirred at 25°C for 3 hours, then heated to 80°C and stirred for 20 hours to obtain a polyimide precursor solution.
[0074] To 100 parts by mass of the solids content of this polyimide precursor solution, 200 parts by mass of polyoxyethylene dimethyl ether (grade: MM400, manufactured by NOF Corporation) with a weight average molecular weight of 400 as a porosifying agent, 4 parts by mass of 2-methylimidazole (2Mz-H, manufactured by Shikoku Chemical Industries Co., Ltd.), and 5091 parts by mass of N-methyl-2-pyrrolidone (NMP) were added and stirred to obtain a homogeneous solution. This solution was applied to copper foil using a die coating method and dried at 120°C for 7 minutes to produce a precursor film with a phase-separated structure approximately 60 μm thick.
[0075] This precursor film was immersed in carbon dioxide pressurized to 30 MPa at 60°C and passed through for 8 hours to promote the extraction and removal of polyoxyethylene dimethyl ether, phase separation of the remaining NMP, and pore formation.The carbon dioxide pressure was then reduced.
[0076] Next, the precursor film was heat-treated under vacuum at a temperature of 300°C to 400°C for approximately 5 hours to remove remaining components and promote imidization, thereby obtaining a porous resin film 1 for metal layer laminates arranged on one thickness-wise surface of the first metal layer 11.
[0077] Thereafter, the first metal layer 11 and the porous resin film 1 for a metal layer laminate were immersed in an FeCl3 solution to dissolve and remove the first metal layer 11. This produced a porous resin film 1 for a metal layer laminate. The dielectric constant and dielectric loss tangent of the porous resin film 1 for a metal layer laminate at a frequency of 60 GHz were 1.51 and 0.006, respectively.
[0078] Table 1 shows the molar fraction of the tertiary diamine (APAB) and the number of parts by mass of the porosifying agent blended for each of the Examples and Comparative Examples.
[0079] <Evaluation> The porous resin films 1 for metal layer laminates of the respective Examples and Comparative Examples were evaluated for the following items. The results are shown in Table 1.
[0080] (Porosity of porous resin film 1 for metal layer laminate) The porosity of the porous resin film 1 for metal layer laminates was calculated based on the following formula.
[0081] Dielectric constant of porous resin film for metal layer laminate 1 = dielectric constant of air × porosity + dielectric constant of polyimide × (1 - porosity) Here, the dielectric constant of air is 1 and the dielectric constant of polyimide is 3.5, so Dielectric constant of porous resin film 1 for metal layer laminates = porosity + 3.5 (1 - porosity) Porosity=(3.5-dielectric constant of porous resin film 1 for metal layer laminate) / 2.5 Porosity (%) = [(3.5 - dielectric constant of porous resin film 1 for metal layer laminate) / 2.5] x 100
[0082] (Minimum thermal expansion coefficient X of porous resin film 1 for metal layer laminates) The porous resin film 1 for metal layer laminates was cut to a size of 4 mm x 40 mm to prepare a sample. The sample was placed in a thermomechanical analyzer (TA Instruments TMA Q400), and the sample was heated from 0 ° C to 200 ° C at a heating rate of 2.0 ° C / min while applying a load of 0.01 N in the in-plane direction, and then cooled from 200 ° C to 0 ° C at a heating rate of 5.0 ° C / min. The sample was then heated from 0 ° C to 200 ° C at a heating rate of 2.0 ° C / min, and the average thermal expansion coefficient from 0 ° C to 200 ° C was determined. The average thermal expansion coefficients were determined for multiple in-plane directions, and the minimum value among them was determined as the minimum thermal expansion coefficient X.
[0083] (Thermal expansion coefficient Z in the thickness direction of the porous resin film 1 for metal layer laminates) The porous resin film 1 for metal layer laminates was cut to a size of 5 mm x 5 mm to prepare a sample. The sample was set in a laser thermal dilatometer (ULVAC-RIKO, LIX-1 laser thermal dilatometer), and the sample was preheated to 200°C before measurement was started. Measurements were performed under conditions of a constant temperature increase rate of 2°C / min in helium, with a load of approximately 17 g applied in the thickness direction over a temperature range of -65°C to 200°C.
[0084] The formulas for calculating the minimum thermal expansion coefficient X and the thermal expansion coefficient Z are as follows: T: Temperature (25℃) L0: Sample length at 25°C L: Amount of expansion from the reference temperature L / L0: Linear expansion coefficient from the reference temperature to each temperature Thermal expansion coefficient = {(ΔL / L0)T1-(ΔL / L0)T2} / (T1-T2)
[0085] <Damage to conductive parts> Through holes were formed in the porous resin film 1 for metal layer laminates by drilling. The through holes were circular in plan view and had a diameter of 300 μm. Then, a conductive part 5 made of copper was formed on the inner surface of the through hole by electroless copper plating and electrolytic copper plating to prepare a sample. The conductive part 5 had a thickness of 10 μm.
[0086] The resistance value of this sample was measured during a temperature cycle test (a thermal cycle test in which the temperature alternated between −65° C. and 150° C.) to detect cracks in the conductive portion 5. Damage to the conductive portion 5 was evaluated according to the following criteria.
[0087] <Standards> ◯: No cracks occurred in the conductive portion 5 until 2000 cycles. Δ: Cracks appeared in the conductive portion 5 within 2000 cycles but more than 1000 cycles. ×: A crack occurred in the conductive portion 5 within 1000 cycles.
[0088] [Table 1] [Explanation of symbols]
[0089] X Minimum coefficient of thermal expansion Z coefficient of thermal expansion
Claims
1. A porous resin film for a metal layer laminate used for laminating a metal layer, The polyimide resin is a reaction product of a diamine component and an acid dianhydride component, the diamine component includes a diamine containing a plurality of aromatic rings and ester bonds disposed therebetween; A minimum thermal expansion coefficient X in a plane direction perpendicular to the thickness direction and a thermal expansion coefficient Z in the thickness direction, A porous resin film for metal layer laminates, wherein the ratio (Z / X) of the thermal expansion coefficient Z in the thickness direction to the minimum thermal expansion coefficient X is 3.5 or less.
2. The porous resin film for metal layer laminates according to claim 1, having through holes penetrating in the thickness direction; a metal layer disposed on one surface and the other surface in the thickness direction of the porous resin film for a metal layer laminate and on the inner peripheral surface of the through hole; A metal layer laminate comprising:
Citation Information
Patent Citations
Polyimide film having improved adhesiveness and its production
JP1999228715A
Porous film for use in wiring board and wiring board prepreg
JP2003201364A
Laminate for wiring board
JP2009004720A
Laminated body for thermally-conductive flexible boards, and thermally-conductive polyimide film
JP2009096192A
Polyimide sheet
JP2011167905A
